Epidemiology of, and behavioural risk factors for, sexually transmitted human papillomavirus infection in men and women in Britain. Issue 3 (17th January 2012) - Johnson, Anne M; Mercer, Catherine H; Beddows, Simon; de Silva, Natasha; Desai, Sarika; Howell-Jones, Rebecca; Carder, Caroline; Sonnenberg, Pam; Fenton, Kevin A; Lowndes, Catherine; Soldan, Kate
Abstract : Objectives: Persistent infection with high-risk sexually transmitted human papillomaviruses (HR-HPVs) can lead to development of cervical and other cancers, while low-risk types (low-risk HPV) may cause genital warts. We explored the epidemiology of different HPV types in men and women and their association with demographic and behavioural variables. Methods: We analysed data collected for the British National Survey of Sexual Attitudes and Lifestyles, a cross-sectional survey undertaken in 1999–2001. Half of all sexually experienced male and female respondents aged 18–44 years were invited to provide a urine sample. We tested 3123 stored urine samples using an in-house Luminex-based HPV genotyping system. Results: HPV DNA was detected in 29.0% (95% CI 26.7% to 31.3%) of samples from women and 17.4% (95% CI 15.1% to 19.8%) from men. Any of 13 HR-HPV types was detected in 15.9% (95% CI 14.1% to 17.8%) of women and 9.6% (95% CI 8.0% to 11.6%) of men. HPV types 16/18 were found in 5.5% (95% CI 4.5% to 6.8%) of women and 3.0% (95% CI 2.1% to 4.3%) of men; and types 6/11 in 4.7% (95% CI 1.8% to 5.9%) of women and 2.2% (95% CI 1.5% to 3.1%) of men. In multivariate analysis, HR-HPV was associated with new partner numbers, in women with younger age, single status and partner concurrency, and in men with number of partners without using condom(s) and age at first intercourse. Conclusions: HPV DNA was detectable in urine of a high proportion of the sexually active British population. In both genders, HR-HPV was strongly associated with risky sexual behaviour. The minority of HPV infections were of vaccine types. It is important to monitor HPV prevalence and type distribution following the introduction of vaccination of girls.